Theoretical, ab initio and DFT, study of the structure and vibrational analysis of Raman, IR and INS spectra of (CH3)3SiNCO - Fernández Liencres, M.P. (2006)
The molecular geometry for trimethylsilylisocyanate ((CH3)3SiNCO) has been calculated at MP2 and DFT/B3LYP and DFT/B3PW91 methods, and using the 6-31G*, 6-311G**, 6-311++G**, cc-pVDZ and cc-pVTZ basis sets. The equilibrium structure of the molecule, linear or bent as concerns the -SiNCO moiety, was found to rely on the method employed. The potential energy surface of -SiNC bending has been investigated by quantum mechanical ab initio calculations at MPn (n = 2-4) and QCISD(T) levels of theory with the cc-pVTZ basis set. This large amplitude bending motion (the υ24 mode) was determined to be very anharmonic, with a low barrier to linearity of the SiNCO skeleton of ∼4-25 cm-1. New vapour and liquid IR, liquid Raman spectra and, for first time, INS spectrum have been recorded, and a complete vibrational assignment has been performed. INS data have allowed to assign two modes at 674 cm-1 and 141 cm-1 which, so far, have been considered as silent, i.e. A2, since previous authors have used a frame of C3v symmetry for this system. The intermolecular interactions show to have little effect on the torsional region (below 250 cm-1 in INS spectrum) and the isolated-molecule approximation works well in that region. A normal coordinate analysis has been carried out by scaling the force fields calculated at MP2/6-311++G** and B3LYP/cc-pVDZ levels of theory using the scaled quantum mechanical force field (SQMFF) methodology. In order to get the best possible agreement between calculated and observed vibrational wavenumbers, the scale factors were refined by least squares yielding a final r.m.s. of ≈7 cm-1. © 2006 Elsevier B.V. All rights reserved.